051 The ACUTE (ambulance CPAP: use, treatment effect and economics) feasibility study: a pilot randomised controlled trial of prehospital CPAP for acute respiratory failure. Issue 12 (21st November 2019) - Fuller, Gordon; Keating, Sam; Goodacre, Steve; Herbert, Esther; Perkins, Gavin; Ward, Matthew; Rosser, Andy; Gunson, Imogen; Miller, Josh; Bradburn, Mike; Harris, Tim; Marsh, Maggie; et al.
Abstract : Background: Acute respiratory failure (ARF) is a common and life-threatening medical emergency. Continuous positive airway pressure (CPAP) is a potentially beneficial prehospital treatment, but it is uncertain whether this could improve important outcomes in NHS ambulance services. Methods: An individually randomised, external pilot study was conducted to test the feasibility of a definitive pragmatic trial. Adults with respiratory distress and peripheral oxygen saturations below British Thoracic Society target levels were recruited from the West Midlands Ambulance Service between August 2017 and July 2018. Participants were randomised 1:1 to prehospital CPAP or standard oxygen therapy. Feasibility objectives estimated the: incidence of eligible patients; proportion recruited and allocated to treatment appropriately; adherence to allocated treatment; retention and data completeness; and 30-day mortality, as a potential primary outcome for a definitive trial. Results: Over 12 months, 77 patients were enrolled (CPAP arm 42, standard oxygen arm 35 cases, target 120). CPAP was fully delivered as planned in 74% (target 75%). There were no major protocol violations/non-compliances (target 0%). Full data were available for key outcomes (target ≥90%). Mortality was higher than expected (overall 27.3%, CPAP arm 28.6% n=12/42, standard care arm 25.7% n=9/35). Of deceased patients, 14/21 (68%) either did not have a respiratory condition or had ceiling of treatment decisions excluding hospital non-invasive ventilation and critical care. Two patients required emergency department treatment for a pneumothorax, neither having received prehospital CPAP. There were no other serious adverse events. Conclusions: The lower than expected recruitment rate, limited compliance with CPAP, and the difficulty in identifying patients who could benefit from CPAP, indicate limited potential for prehospital CPAP to reduce mortality. A definitive effectiveness trial is therefore not recommended. These findings also argue against routine implementation of CPAP into NHS ambulance services.